Sosialisasi Anti-Bullying kepada Masyarakat Desa Banaran, Kecamatan Sambungmacan, Kabupaten Sragen Sebagai Bentuk Implementasi Poin 4 Sustainable Development Goals (SDGs) Di Indonesia - Probosambodo, Yokhebed Arumdika; Doyoharjo, Anggo (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The importance of anti-bullying outreach in achieving Sustainable Development Goals (SDGs) point 4, namely quality education that is inclusive and fair. Bullying, both in schools and colleges, threatens the safe and supportive learning environments needed to achieve these goals. The family as the "first school" has a crucial role in preventing bullying. In a family environment, children are taught values such as empathy, understanding and honesty which are important to prevent bullying behavior. Parents and other family members serve as role models for children to demonstrate positive ways of interacting and respecting others. Apart from that, families also teach children how to provide quality education, manage conflict constructively, so that they have strong social and emotional skills to deal with various situations, including bullying. In this way, the family provides a solid foundation for children to grow into individuals who are empathetic and care about the welfare of others.